Experiences of Patients With Borderline Personality Disorder With Imagery Rescripting in the Context of Schema Therapy—A Qualitative Study - Schaich, Anja; Braakmann, Diana; Richter, Anja; Meine, Clara; Assmann, Nele; Köhne, Sandra; Arntz, Arnoud; Schweiger, Ulrich; Fassbinder, Eva (Frontiers in Psychiatry, 2020)
Abstract Imagery Rescripting (IR) is a therapeutic technique that is used in a wide spectrum of therapeutic methods for various mental disorders. As an important component of Schema therapy (ST), IR is frequently used in the treatment of patients with borderline personality disorder (BPD). However, little is known about how IR is experienced by individuals with BPD. The aim of this study was to explore BPD patients’ experiences with receiving IR. Qualitative data were collected through semi-structured interviews with 21 individuals (86% females) with a primary diagnosis of BPD who received IR within their ST treatment. Interview data were analyzed following the procedures of qualitative content analysis. Participants reported various effects of IR including initial high emotionality and exhaustion. Long-term effects included a better understanding of schemas and an improvement regarding emotion regulation and interpersonal relationships. Participants reported factors hindering the successful implementation of IR such as external noise, stress and a fast pace during IR. Facilitating factors included adequate time for debriefing, a transparent structure and preparation of IR as well as the therapist providing safety. Implications of the findings for optimizing IR in clinical practice are discussed.